2018
DOI: 10.1007/s13311-018-0611-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-herpetic Medications and Reduced Risk of Dementia in Patients with Herpes Simplex Virus Infections—a Nationwide, Population-Based Cohort Study in Taiwan

Abstract: This retrospective cohort study is to investigate the association between herpes simplex virus (HSV) infections and dementia, and the effects of anti-herpetic medications on the risk involved, using Taiwan's National Health Insurance Research Database (NHIRD). We enrolled a total of 33,448 subjects, and identified 8362 with newly diagnosed HSV infections and 25,086 randomly selected sex- and age-matched controls without HSV infections in a ratio of 1:3, selected from January 1, to December 31, 2000. A multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
253
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(270 citation statements)
references
References 60 publications
(70 reference statements)
14
253
2
1
Order By: Relevance
“…The re-emergence of HHV-6A in this new dataset provides an encouraging consistency in viral signal. In combination with the findings of many other investigators 3,4,6,7,13,[15][16][17][18][19][20][21] these new data also support the utility of a systematic, coordinated effort to characterize the brain microbiome in AD.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…The re-emergence of HHV-6A in this new dataset provides an encouraging consistency in viral signal. In combination with the findings of many other investigators 3,4,6,7,13,[15][16][17][18][19][20][21] these new data also support the utility of a systematic, coordinated effort to characterize the brain microbiome in AD.…”
Section: Introductionsupporting
confidence: 72%
“…These reports have accelerated even further recently, including reports of Herpesviridae induced seeding of Aβ fibrillation in transgenic AD mouse and 3D organoid model systems 3 . In a population-based cohort study in Taiwan, Tzeng et al 4 observed an increased dementia risk following HSV-1 infection. These authors reported that the dementia risk in this cohort post HSV-1 infection appeared to be almost completely abolished by antiviral use.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, a 16-year long study involving over 33,000 patients found HSV1 infection increases AD risk 2.5 fold (Tzeng et al, 2018). Moreover, long-term administration of anti-herpetic medications appears to reduce AD risk for HSV1 infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent studies carried out on genital herpes infections have been linked to dementia. 10 Other population-based studies have also shown that viral diseases of the skin, such as herpes simplex or herpes zoster infections, were associated with the increased risk of dementia, [11][12][13][14][15][16] and some studies have observed that treatment with antiherpetic antiviral medications could attenuate the risk of developing dementia in patients with herpetic virus infection. 17,18 Several studies have shown that HPV may be detected in neurological diseases, for example, in the brains of patients with pediatric epilepsy 19,20 and Rasmussen's encephalitis.…”
Section: Introductionmentioning
confidence: 99%